Failure to detect polyalbumin-binding sites on the woodchuck hepatitis virus surface antigen: implications for the pathogenesis of hepatitis B virus in humans. - Pohl, C J (1986)
Binding sites for polymerized albumin on hepatitis B virus components were reported in human hepatitis B virus chronic carriers predominantly with active viral replication (HB e antigen positive). The presence of comparable albumin-binding sites in the woodchuck hepatitis virus (WHV) model was examined on WHV components obtained from woodchucks with active viral replication (DNA polymerase positive). Binding sites for polymerized woodchuck serum albumin were not detected on the intact WHV virion, on 22-nm woodchuck hepatitis surface antigen (WHsAg), or on WHsAg polypeptides. Woodchuck albumin was not detected in purified 22-nm WHsAg, and anti-albumin antibodies were not detected in WHV chronic-carrier woodchucks. Our results in the WHV model argue against a role for viral polyalbumin-binding sites in tissue- and host-specific virus infectivity.